EVALUATING THE IMPACT OF WILDLIFE PROTECTION LAWS IN INDIA: A CASE STUDY OF TADOBA ANDHARI TIGER RESERVE, CHANDRAPUR DISTRICT - Sheikh, Niyaj Shabbir; Shaikh, Dr. Aejaz (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Tadoba Andhari Tiger Reserve and similar protected areas play a crucial role in maintaining India’s rich biodiversity. Focusing specifically on TATR in Maharashtra, this investigation analyzes the effectiveness of wildlife conservation laws in India. It examines the impacts of pivotal legislation like the Wildlife Protection Act of 1972 on public involvement, poaching control and species protection. This research aims to address current policy shortcomings and barriers by scrutinizing outcomes, implementation techniques and legal frameworks. Secondary sources such as field observations, official reports and stakeholder interviews may provide insights into how successful preservation efforts have been. While protective frameworks have aided in better safeguarding wildlife, the study results indicate that human-animal conflicts, insufficient enforcement and policy gaps remain substantial issues. In concluding their examination, the authors put forth proposals for how wildlife preservation in India could be strengthened through employing technology, boosting community participation and stricter law implementation.